The Effect of Accreditation Results on The Quality of Academic Services in Early Children Education Institutions in Pati District - Ismi, Anasta Dian; Waluyo, Edi (BELIA: Early Childhood Education Papers, 2021)
According to interests, fulfilling the community's needs, one of which provides a good quality service sector with quality schools, is an essential thing in education. In the Pati District, there are still many early childhood education institutions that have not been accredited. This does not rule out the possibility that the quality of academic services in each institution is still low. This study aimed to determine the differences in the quality of academic services for Early Childhood Education institutions at accredited schools A, B and C in Pati District. The research approach used is comparative quantitative with ex post facto design. In this study, subjects were parents who have children who attend accredited kindergartens in Pati, totalling 95 subjects. The samples were taken using the Proportional Stratified Random Sampling technique. The data collection technique uses a scale of academic service quality. The data analysis technique used is the non-parametric statistical hypothesis test using the Kruskal-Wallis test using the SPSS 25 program. The study results found that there were differences in the quality of academic services between Kindergartens accredited A, B and C. accredited A has a mean rank value of 71.70, the quality of Kindergarten academic services accredited B has a mean rank value of 30.85. In contrast, the quality of Kindergarten academic services accredited C has a mean rank value of 2.00. This means that the higher the level of accreditation, the higher the quality of academic services.